KONSEP KESETARAAN GENDER DALAM ISLAM: Studi terhadap Pemikiran Hermeneutika Muhammad Syahrur - Rohmatul Izzad (STAI AL-ANWAR SARANG, 2018)
Abstract From the 20th century to the 21st century, feminist model of interpretation has been developing rapidly. The majority of feminist interpreters, both men and women, criticize the centrality of men in interpreting the Qur'an.They emphasize the argument that the interpreter's gender bias is still dominated by men, most of which have shaped the paradigm of understanding the Qur'an and Islam in general. In contrast to secular feminists, Muslim feminist scholars do not reject Islam itself. Instead, they refer to the Qur'an and the Prophet's Sunnah to support their claim that the Qur'an needs to be reinterpreted. This research specifically tries to study and explore the concept of gender equality in Islam, especially in the perspective of Muhammad Syahrur's hermeneutic thinking. This research analyzes the real relationship between men and women in Islam, whether the views of past scholars are still relevant in positioning the status of men and women. In other words, this research tries to carry out a contemporary reading of the gender equality concept in Islam, which specifically refers to Muhammad Syahrur's hermeneutic. On this basis, this study uses an analysis-hermeneutic approach. Through Syahrur's hermeneutics, the researcher critically analyzes the relationship between men and women in Islam, and carries out a contemporary reading of it. Therefore it is expected to be able to produce a new thought product about gender in Islam that is more contextual and in accordance with the dynamics of the times. Keywords: feminism, gender equality, al-Qur'an hermeneutics.